Coronary Artery Bypass Grafting in a Patient with Dextrocardia with Situs Inversus. (14th December 2020) - Woods, Kaitlin E.; Awori Hayanga, J. W.; Sloyer, Daniel; Henrickson, Roy E.; Wei, Lawrence M.; Hayanga, Heather K.
Abstract : Dextrocardia involves embryologic malformations leading to a right hemithorax heart with rightward apex. Situs inversus encompasses all viscera in mirrored position. A 76-year-old male with dextrocardia with situs inversus presented for coronary artery bypass grafting due to a non-ST elevation myocardial infarction. Management was altered accordingly. Electrocardiography leads and defibrillator pads were reversed. A left internal jugular vein central venous catheter provided direct access to the right atrium. Transesophageal echocardiography confirmation of aortic and venous cannulation required turning the probe right for the right-sided aorta and left for liver visualization, respectively. Proactive surgical and anesthetic management was imperative for the successful and uneventful outcome for this patient.